Bacterial Community Structure after Long-term Organic and Inorganic Fertilization Reveals Important Associations between Soil Nutrients and Specific Taxa Involved in Nutrient Transformations - Li, Fang; Chen, Lin; Zhang, Jiabao; Yin, Jun; Huang, Shaomin (Frontiers in Microbiology, 2017)
Fertilization has a large impact on the soil microbial communities, which play pivotal roles in soil biogeochemical cycling and ecological processes. While the effects of changes in nutrient availability due to fertilization on the soil microbial communities have received considerable attention, specific microbial taxa strongly influenced by long-term organic and inorganic fertilization, their potential effects and associations with soil nutrients remain unclear. Here we use deep 16S amplicon sequencing to investigate bacterial community characteristics in a fluvo-aquic soil treated for 24 years with inorganic fertilizers and organics (manure and straw)-inorganic fertilizers, and uncover potential links between soil nutrient parameters and specific bacterial taxa. Our results showed that combined organic-inorganic fertilization increased soil organic carbon (SOC) and total nitrogen (TN) contents and altered bacterial community composition, while inorganic fertilization had little impact on soil nutrients and bacterial community composition. SOC and TN emerged as the major determinants of community composition. The abundances of specific taxa, especially Arenimonas, Gemmatimonas and an unclassified member of Xanthomonadaceae, were substantially increased by organic-inorganic amendments rather than inorganic amendments only. A co-occurrence based network analysis demonstrated that SOC and TN had strong positive associations with some taxa (Gemmatimonas and the members of Acidobacteria subgroup 6, Myxococcales, Betaproteobacteria and Bacteroidetes), and Gemmatimonas, Flavobacterium and an unclassified member of Verrucomicrobia were identified as the keystone taxa. These specific taxa identified above are implicated in the decomposition of complex organic matters and soil carbon, nitrogen and phosphorus transformations. The present work strengthens our current understanding of the soil microbial community structure and functions under long-term fertilization management and provides certain theoretical support for selection of rational fertilization strategies.